Szacowanie kosztu kapitału w Polsce - konfrontacja teorii z praktyką - Byrka-Kita, Katarzyna (Estimating the Cost of Capital in Poland - Practice Versus Theory, 2008)
This paper presents the results of the cost-of-capital survey of 500 managers of the biggest (according to Rzeczpospolita) Polish companies. Contrary to the tendencies in developed markets where can be observed close alignment among managers on the use of common theoretical frameworks and on many aspects of estimation, the results of the research carried out in the Polish market are different -there is a substantial gap between the cost-of-capital theory and the procedures applied by the Polish managers.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 92-99